Cytomegalovirus-Related Splenic Infarcts: Viral Twist and a Vascular Phenomenon - Parth Adrejiya; Mohammad Abubaker; Viraj Panchal; Lewam Berhe; Komal Harisinghani; Rand Daoud; Srikanth Maddika; Rushi Patel (Annals of Internal Medicine: Clinical Cases)
Cytomegalovirus (CMV) infections in an individual who is immunocompetent can range from asymptomatic to infectious mononucleosis syndrome. More severe complications are seen in individuals who are immunocompromised, and these complications are associated with life-threatening conditions. One of them is CMV-associated thrombosis, commonly seen in individuals who are immunocompromised, who are transplant recipients, or who are people living with HIV/AIDS. In this case report, we present a unique case of acute CMV infection in a 35-year-old healthy individual who is immunocompetent and who developed the rare complication of isolated splenic infarction.